Method for evaluating volume change rate of martensite and austenite dual-phase steel after heat treatment
Through XRD test and formula calculation, the volume change rate of martensite austenitic double-phase steel after heat treatment is evaluated, which solves the problem of difficulty in evaluating the volume change rate in the prior art and improves the ability to regulate material dimensional stability.
Patent Information
- Application Number
- CN202411987125.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to effectively evaluate the volume change rate of martensite austenitic duplex steel after heat treatment, which limits the deeper research on material dimensional stability and the guidance of manufacturing processes.
The diffraction peak intensity of martensite and austenite was obtained through the XRD test, and the volume percentage was calculated, and the lattice constant was combined with the specific formula to calculate the volume change rate after heat treatment.
The accurate evaluation of the volume change rate after heat treatment of martensite austenitic dual-phase steel is achieved, and the ability to regulate the dimensional stability of the material is improved, helping to avoid the dimensional instability of the material in various environments.
Smart Images

Figure CN119901767A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material dimensional stability evaluation, and in particular relates to a method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment. Background Art
[0002] With the continuous advancement of manufacturing technology, steel is not only used as a basic raw material in the construction, manufacturing, automobile, energy and other industries, but also used in new industries such as 3D printing and precision machining. Its dimensional stability directly affects the quality, manufacturing efficiency and final use of the product. For industries such as precision engineering, aerospace, and high-end machinery, the dimensional stability of steel is extremely high, and dimensional stability is a key factor in ensuring product quality and production efficiency.
[0003] The dimensional stability of martensite-austenite dual-phase steel is one of the main factors affecting the service life of the workpiece. In order to ensure the material accuracy and improve the material life, more stringent requirements are put forward for the dimensional stability of the material. Good dimensional stability is crucial to improving the service life, safety, reliability and operating efficiency of equipment under harsh working conditions.
[0004] At present, the research on the dimensional stability of martensite-austenite dual-phase steel is relatively superficial, which limits the in-depth research on the dimensional stability of dual-phase steel materials. It is well known that the volume of martensite-austenite dual-phase steel will change to a certain extent after heat treatment, but there is no specific assessment standard for the specific volume change. Therefore, people do not know the specific volume change of dual-phase steel materials after a certain process heat treatment, and cannot conduct deeper research, nor can they guide the specific manufacturing process. Summary of the invention
[0005] To solve the above problems, the present invention provides a method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment. According to the phase transformation conversion and corresponding volume change of martensite-austenite dual-phase steel during the heat treatment process, the volume change rate of martensite-austenite dual-phase steel after heat treatment is calculated, and the influence of different heat treatment processes on the dimensional stability of martensite-austenite dual-phase steel is analyzed, so as to effectively improve the ability to regulate the dimensional stability of materials, and to a certain extent, help avoid the dimensional instability of materials in various environments.
[0006] The present invention is specifically implemented by the following technical scheme. According to a method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment proposed by the present invention, it comprises the following steps:
[0007] (1) An XRD test was performed on a martensite-austenite dual-phase steel sample (hereinafter referred to as the "original dual-phase steel sample"). The parameters of the XRD test include the diffraction peak intensities of martensite and austenite in the original dual-phase steel sample: Iγ`(200), Iγ`(220), Iγ`(311), Iα`(200), and Iα`(211), where α represents martensite and γ represents austenite; Iγ`(200) represents the diffraction peak of the austenite (200) crystal plane in the original dual-phase steel sample. intensity, Iγ`(220) represents the diffraction peak intensity of the austenite (220) crystal plane in the original dual-phase steel sample, Iγ`(311) represents the diffraction peak intensity of the austenite (311) crystal plane in the original dual-phase steel sample, Iα`(200) represents the diffraction peak intensity of the martensite (200) crystal plane in the original dual-phase steel sample, and Iα`(211) represents the diffraction peak intensity of the martensite (211) crystal plane in the original dual-phase steel sample; the volume percentage V' of austenite in the original dual-phase steel sample is calculated γ and the volume percentage of martensite V' α ;
[0008] (2) heat treating the original dual-phase steel sample of step (1), and performing XRD test on the heat treated sample, the method and test conditions are the same as step (1); the test parameters include the diffraction peak intensities of martensite and austenite in the heat treated sample Iγ(200), Iγ(220), Iγ(311), Iα(200), and Iα(211), wherein α represents martensite and γ represents austenite; Iγ(200) represents the diffraction peak intensities of austenite (200) in the heat treated sample. The diffraction peak intensity of the austenite (220) crystal plane in the heat-treated sample is Iγ(220), the diffraction peak intensity of the austenite (311) crystal plane in the heat-treated sample is Iγ(311), the diffraction peak intensity of the martensite (200) crystal plane in the heat-treated sample is Iα(200), and the diffraction peak intensity of the martensite (211) crystal plane in the heat-treated sample is Iα(211). The volume percentage of austenite in the heat-treated sample V" is calculated. γ and the volume percentage of martensite V" α ;
[0009] (3) The volume percentage of martensite in the original dual-phase steel sample V' α and the volume percentage of austenite V' γ , Volume percentage of martensite in the sample after heat treatment V" α and the volume percentage of austenite V" γ and the martensite lattice constant a α and austenite lattice constant a γ Substitute into formula (2) The volume change rate of martensite-austenite dual-phase steel after heat treatment was calculated.
[0010] In the aforementioned method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment, the metal target in the XRD test process is a Co target.
[0011] The aforementioned method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment is to calculate the volume percentage V' of austenite in the original dual-phase steel sample according to the five-line six-pair method in the ferrous metallurgy industry standard YB / T 5338-2019 of the People's Republic of China. γ And the volume percentage of austenite in the sample after heat treatment V" γ , the volume percentage of austenite in the original dual-phase steel sample V' γ , the volume percentage of austenite in the sample after heat treatment V" γ Substitute into formula (1) V γ +V α =100%, and the volume percentage of martensite in the original dual-phase steel sample V' is calculated respectively. α , Volume percentage of martensite in the sample after heat treatment V" α ; The martensite lattice constant a is obtained according to the standard PDF card in the International Diffraction Data Center database α and austenite lattice constant a γ .
[0012] Furthermore, according to the five-line six-pair method in YB / T 5338-2019, according to formula (3) Calculate the volume percentage V of austenite in the sample γ In formula (3), V γ is the volume percentage of austenite in the sample, V c Indicates the volume percentage of the total amount of carbide phase in the sample. The carbon content of the martensite-austenite dual-phase steel used in the experiment is less than 0.01%. c Ignore, so V c =0; Indicates the martensite phase in the sample (hkl) i The diffraction peak intensity of the crystal plane; Indicates the austenite phase in the sample after heat treatment (hkl) i Diffraction peak intensity of crystal plane; G represents austenite phase (hkl) i Crystal plane and martensite phase (hkl) i The ratio of intensity-related factors corresponding to the crystal planes;
[0013] The G value, the ratio of the diffraction peak intensity of martensite to austenite in the original dual-phase steel sample Substituting into formula (3), we can obtain the volume percentage V' of austenite in the original dual-phase steel sample: γ; The G value and the ratio of the diffraction peak intensity of martensite to austenite in the heat treated sample Substituting into formula (3), we can obtain the volume percentage of austenite in the sample after heat treatment: V” γ .
[0014] Furthermore, the ratio of the diffraction peak intensity of martensite to austenite in the original dual-phase steel sample include Each pair Substitute the value of and the corresponding G value into formula (3) Calculate V' once γ , a total of 6 V' γ value, and then calculate the 6 V' γ The arithmetic mean of the values is the volume percentage V' of austenite in the original duplex steel sample. γ .
[0015] Furthermore, the ratio of the diffraction peak intensity of martensite to austenite in the heat treated sample is include Each pair Substitute the value of and the corresponding G value into formula (3) Calculate V once γ , a total of 6 V γ value, and then calculate 6 V" γ The arithmetic mean of the values is the volume percentage V" of austenite in the sample after heat treatment. γ .
[0016] The aforementioned method for evaluating the volume change rate of martensitic-austenitic dual-phase steel after heat treatment can use a resistance furnace with a model of BSK-83 and a rated power of 9KW to heat treat the martensitic steel sample, but the present invention is not limited thereto.
[0017] The aforementioned method for evaluating the volume change rate of martensitic austenitic dual-phase steel after heat treatment can be used to heat treat the martensitic steel sample in a resistance furnace with a model of BSK-83 and a rated power of 9KW, heating the temperature to 500-600°C at a heating rate of 10°C / min, keeping the temperature at 500-600°C for 180 minutes, then taking out the sample and cooling it to room temperature in the air to obtain a heat-treated sample, but the present invention is not limited to this.
[0018] Further, the temperature of the heat treatment is 500° C., 550° C., or 600° C., but the present invention is not limited thereto.
[0019] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages:
[0020] According to the phase transformation and corresponding volume change of martensite-austenite dual-phase steel during heat treatment, the volume percentage V' of martensite in the original dual-phase steel sample is calculated. α and the volume percentage of austenite V' γ , Volume percentage of martensite in the sample after heat treatment V" α and the volume percentage of austenite V" γ and the martensite lattice constant a α and austenite lattice constant a γ Substituting the formula into the calculation, the volume change rate of the martensite-austenite dual-phase steel after heat treatment is obtained. The volume change of the martensite-austenite dual-phase steel after heat treatment can be obtained through the size of the volume change rate, thereby preliminarily predicting the stability of the martensite-austenite dual-phase steel after heat treatment, effectively improving the ability to regulate the dimensional stability of the material, assisting the existing macroscopic dimensional stability test method, and to a certain extent, helping to avoid the dimensional instability of the material in various environments. The present invention can also reduce the experimental design and prediction costs, effectively guide the manufacturing process, avoid the dimensional instability of the material, and has high flexibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 1 is a microstructure diagram (OM diagram) of the original martensite-austenite dual-phase steel sample and the dual-phase steel sample after the process heat treatment of Examples 1 to 3 under an optical microscope, wherein (a) represents the original martensite-austenite dual-phase steel sample, (b), (c), and (d) correspond to the dual-phase steel samples after the process heat treatment of Examples 1, 2, and 3, respectively;
[0022] Figure 2 3 are SEM images of the original martensite-austenite dual-phase steel sample and the sample after the process heat treatment of Examples 1 to 3, wherein (a) represents the original martensite-austenite dual-phase steel sample, (b), (c), and (d) correspond to the dual-phase steel samples after the process heat treatment of Examples 1, 2, and 3, respectively. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The present invention provides a method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment, comprising the following steps:
[0025] (1) XRD test was performed on a martensite-austenite dual-phase steel sample (hereinafter referred to as the "original dual-phase steel sample"). During the test, Co target was used as the metal target. The experimental parameters of the XRD test included the diffraction peak intensities of martensite and austenite in the original dual-phase steel sample Iγ`(200), Iγ`(220), Iγ`(311), Iα`(200), and Iα`(211), where α represents martensite and γ represents austenite; Iγ`(200) represents the original dual-phase steel sample. The diffraction peak intensity of the austenite (200) crystal plane in the original dual-phase steel sample, Iγ`(220) represents the diffraction peak intensity of the austenite (220) crystal plane in the original dual-phase steel sample, Iγ`(311) represents the diffraction peak intensity of the austenite (311) crystal plane in the original dual-phase steel sample, Iα`(200) represents the diffraction peak intensity of the martensite (200) crystal plane in the original dual-phase steel sample, and Iα`(211) represents the diffraction peak intensity of the martensite (211) crystal plane in the original dual-phase steel sample. The volume percentage V' of austenite in the original dual-phase steel sample was calculated according to the five-line six-pair method in the ferrous metallurgy industry standard YB / T 5338-2019 of the People's Republic of China. γ According to formula (1) V γ +V α =100% The volume percentage of martensite in the original dual-phase steel sample V' is calculated α .
[0026] (2) The original dual-phase steel sample is heat treated, and the heat-treated sample is subjected to XRD testing, the method and test conditions are the same as step (1). The experimental parameters of the test include the diffraction peak intensities of martensite and austenite in the sample after heat treatment, Iγ(200), Iγ(220), Iγ(311), Iα(200), and Iα(211), where α represents martensite and γ represents austenite; Iγ(200) represents the diffraction peak intensity of the austenite (200) crystal plane in the sample after heat treatment, Iγ(220) represents the diffraction peak intensity of the austenite (220) crystal plane in the sample after heat treatment, Iγ(311) represents the diffraction peak intensity of the austenite (311) crystal plane in the sample after heat treatment, Iα(200) represents the diffraction peak intensity of the martensite (200) crystal plane in the sample after heat treatment, and Iα(211) represents the diffraction peak intensity of the martensite (211) crystal plane in the sample after heat treatment. The volume percentage V of austenite in the heat-treated sample was calculated according to the five-line six-pair method in the ferrous metallurgy industry standard YB / T 5338-2019 of the People's Republic of China. γ According to formula (1) V γ +V α =100% The volume percentage of martensite in the sample after heat treatment is calculated as V" α ;
[0027] (3) The martensite lattice constant a is obtained according to the standard PDF card in the International Diffraction Data Center database.α and austenite lattice constant a γ .
[0028] (4) The volume percentage of martensite in the original dual-phase steel sample V' α and the volume percentage of austenite V' γ , Volume percentage of martensite in the sample after heat treatment V" α and the volume percentage of austenite and V" γ and the martensite lattice constant a α and austenite lattice constant a γ Substitute into formula (2) The volume change rate of the martensite-austenite dual-phase steel after heat treatment is calculated; wherein ΔV% is the volume change rate of the martensite-austenite dual-phase steel after heat treatment.
[0029] Furthermore, the volume percentage of austenite in the original dual-phase steel sample V' γ And the volume percentage of austenite in the sample after heat treatment V" γ The following methods are used for calculation:
[0030] According to the five-line six-pair method in YB / T 5338-2019, according to formula (3) The volume percentage V' of austenite in the original dual-phase steel sample is calculated γ And the volume percentage of austenite in the sample after heat treatment V" γ In formula (3), V γ is the volume percentage of austenite in the sample, V c Indicates the volume percentage of the total amount of carbide phase in the sample (the carbon content of the experimental steel is less than 0.01%, so V c can be ignored, and V c =0), Indicates the martensite phase in the sample (hkl) i The diffraction peak intensity of the crystal plane; Indicates the austenite phase in the sample after heat treatment (hkl) i Diffraction peak intensity of crystal plane; G represents austenite phase (hkl) i Crystal plane and martensite phase (hkl) i The ratio of the intensity-related factors corresponding to the crystal plane is The abbreviation of G is different according to different diffraction. The G values of different diffraction line pairs are shown in Table 1.
[0031] Table 1. G values of different diffraction line pairs (Co target)
[0032] G (200)γ (220)γ (311)γ (200)α 2.46 1.32 1.78 (211)α 1.21 0.65 0.87
[0033] The G value, the ratio of the diffraction peak intensity of martensite to austenite in the original dual-phase steel sample Substitute into formula (3) The volume percentage V' of austenite in the original dual-phase steel sample is obtained γ The G value and the ratio of the diffraction peak intensity of martensite to austenite in the heat treated sample are Substitute into formula (3) Get the volume percentage V" of austenite in the sample after heat treatment γ .
[0034] Furthermore, the ratio of the diffraction peak intensity of martensite to austenite in the original dual-phase steel sample include Each pair Substitute the value of and the corresponding G value into formula (3) Calculate V' once γ , a total of 6 V' γ value, and then calculate the 6 V' γ The arithmetic mean of the values is the volume percentage V' of austenite in the original duplex steel sample. γ .
[0035] The ratio of the diffraction peak intensity of martensite to austenite in the sample after heat treatment include Each pair Substitute the value of and the corresponding G value into formula (3) Calculate V once γ , a total of 6 V" γ value, and then calculate 6 V" γ The arithmetic mean of the values is the volume percentage V" of austenite in the sample after heat treatment. γ .
[0036] The calculated V' γ , V” γ Substitute into formula (1) V γ +V α = 100%, respectively, and the volume percentage of martensite in the original dual-phase steel sample V' is obtained. α and the volume percentage of martensite in the sample after heat treatment V" α .
[0037] The volume change caused by phase transformation during heat treatment of martensite-austenite dual-phase steel is as follows:
[0038]
[0039] Where V' 马 and V'奥 are the volume of martensite and austenite in the original dual-phase steel sample, V' 马 and V' 奥 are the volume of martensite and the volume of austenite in the sample after heat treatment, respectively.
[0040] The volume of martensite and austenite can be calculated by the unit cell number × unit cell volume (V = N × a 3 ) is obtained, that is
[0041]
[0042]
[0043]
[0044]
[0045] therefore,
[0046]
[0047] It can be deduced that
[0048]
[0049] Where N' α and N' γ are the number of martensite cells and austenite cells in the original dual-phase steel sample, N” α and N' γ are the number of martensite cells and austenite cells in the sample after heat treatment. Martensite is a body-centered cubic structure, and austenite is a face-centered cubic structure, containing 2 and 4 atoms respectively. The following relationship exists during the martensite-austenite phase transformation:
[0050] N' α +2N' γ =N” α +2N” γ Formula (13)
[0051] Substituting formula (11) and (12) into formula (13), we get:
[0052]
[0053] It can be deduced that
[0054]
[0055] The volume ratio of martensite to austenite in the original dual-phase steel sample is equal to the volume percentage ratio of martensite to austenite in the original dual-phase steel sample; the volume ratio of martensite to austenite in the heat-treated sample is equal to the volume percentage ratio of martensite to austenite in the heat-treated sample, that is:
[0056]
[0057] Substituting formula (16) and (17) into formula (15), we obtain:
[0058]
[0059] Substituting formulas (5), (6), (7), (8), (11), (12) and (18) into formula (4) yields formula (2):
[0060]
[0061] In formula (2), ΔV% is the volume change rate of martensite-austenite dual-phase steel after heat treatment, V' α and V' γ are the volume percentage of martensite and austenite in the original dual-phase steel sample, V” α and V” γ are the volume percentage of martensite and austenite in the sample after heat treatment, respectively. α is the martensite lattice constant, a γ is the austenite lattice constant.
[0062] The following is a detailed description with specific embodiments:
[0063] Embodiment 1:
[0064] (1) XRD test was performed on a martensite-austenite dual-phase steel sample (hereinafter referred to as the "original dual-phase steel sample"). During the test, Co target was used as the metal target. The experimental parameters of the XRD test included the diffraction peak intensities of martensite and austenite in the original dual-phase steel sample Iγ`(200), Iγ`(220), Iγ`(311), Iα`(200), and Iα`(211), where α represents martensite and γ represents austenite; Iγ`(200) represents the original dual-phase steel sample. Iγ`(220) represents the diffraction peak intensity of the austenite (220) crystal plane in the original dual-phase steel sample, Iγ`(311) represents the diffraction peak intensity of the austenite (311) crystal plane in the original dual-phase steel sample, Iα`(200) represents the diffraction peak intensity of the martensite (200) crystal plane in the original dual-phase steel sample, and Iα`(211) represents the diffraction peak intensity of the martensite (211) crystal plane in the original dual-phase steel sample. The test results are shown in Table 2.
[0065] Table 2. Diffraction peak intensities of martensite and austenite in original dual-phase steel samples
[0066] Iγ`(200) Iγ`(220) Iγ`(311) Iα`(200) Iα`(211) Original duplex steel sample 24100 20147 19786 63872 123824
[0067] According to the five-wire six-pair method in the People's Republic of China Ferrous Metallurgical Industry Standard YB / T 5338-2019, according to formula (3) The volume percentage V' of austenite in the original dual-phase steel sample is calculated γ =16.30%, according to formula (1) V γ +V α =100% The volume percentage of martensite in the original dual-phase steel sample V' is calculated α =83.70%.
[0068] (2) The original dual-phase steel sample of step (1) is placed in a BSK-83 resistance furnace with a rated power of 9 kW for heat treatment. The resistance furnace is heated to 500°C at a heating rate of 10°C / min and kept at this temperature for 180 min. The sample is then taken out and placed in air to cool to room temperature to obtain a heat-treated sample. The heat-treated sample was subjected to XRD test, and the method and test conditions were the same as step (1), and the diffraction peak intensities of martensite and austenite in the heat-treated sample were obtained, Iγ(200), Iγ(220), Iγ(311), Iα(200), and Iα(211), where α represents martensite and γ represents austenite; Iγ(200) represents the diffraction peak intensity of the austenite (200) crystal plane in the heat-treated sample, Iγ(220) represents the diffraction peak intensity of the austenite (220) crystal plane in the heat-treated sample, Iγ(311) represents the diffraction peak intensity of the austenite (311) crystal plane in the heat-treated sample, Iα(200) represents the diffraction peak intensity of the martensite (200) crystal plane in the heat-treated sample, and Iα(211) represents the diffraction peak intensity of the martensite (211) crystal plane in the heat-treated sample. The test results are shown in Table 3.
[0069] According to the five-wire six-pair method in the People's Republic of China Ferrous Metallurgical Industry Standard YB / T 5338-2019, according to formula (3) The volume percentage V" of austenite in the sample after heat treatment at 500℃ was calculated γ =26.01%, according to formula (1) V γ +V α =100% The volume percentage of martensite in the sample after heat treatment at 500℃ is calculated as V" α =73.99%. According to the standard PDF card in the International Diffraction Data Center database, the martensite lattice constant a is obtained: α =2.873, austenite lattice constant a γ =3.593, that is
[0070] (3) V' α 、V' γ , V” α , V” γ , Substitute the value of into formula (2) The volume change rate of the martensite-austenite dual-phase steel after heat treatment at 500°C is calculated to be ΔV% = -0.217%.
[0071] Embodiment 2:
[0072] (1) Same as in Example 1;
[0073] (2) The original dual-phase steel sample was placed in a BSK-83 resistance furnace with a rated power of 9KW for heat treatment, and the temperature was raised to 550°C at a heating rate of 10°C / min and kept at this temperature for 180 minutes. Then the sample was taken out and placed in the air to cool to room temperature to obtain a heat-treated sample. The heat-treated sample was subjected to XRD testing. The remaining steps and calculation methods were the same as those in Example 1. The diffraction peak intensity data of martensite and austenite in the sample after heat treatment at 550°C in this embodiment were obtained, as shown in Table 3. According to the five-line six-pair method in the ferrous metallurgy industry standard YB / T 5338-2019 of the People's Republic of China, according to formula (3): The volume percentage V" of austenite in the sample after heat treatment at 550℃ was calculated γ =28.41%, according to formula (1) V γ +V α =100% The volume percentage of martensite in the sample after heat treatment at 550℃ is calculated as V" α =71.59%. The martensite lattice constant and austenite lattice constant remain unchanged, that is, a α =2.873, a γ =3.593,
[0074] (3) V' α 、V' γ , V” α , V” γ , Substitute the numerical value into formula (2): The volume change rate of the martensite-austenite dual-phase steel after heat treatment at 550°C is calculated to be ΔV% = -0.271%.
[0075] Embodiment 3:
[0076] (1) Same as in Example 1;
[0077] (2) The original dual-phase steel sample was placed in a BSK-83 resistance furnace with a rated power of 9KW for heat treatment, and the temperature was raised to 600°C at a heating rate of 10°C / min and kept at this temperature for 180 minutes. Then the sample was taken out and placed in the air to cool to room temperature to obtain a heat-treated sample. The heat-treated sample was subjected to XRD test. The remaining steps and calculation methods were the same as those in Example 1. The diffraction peak intensity data of martensite and austenite in the sample after heat treatment at 600°C in this embodiment were obtained, as shown in Table 3. According to the five-line six-pair method in the ferrous metallurgy industry standard YB / T 5338-2019 of the People's Republic of China, according to formula (3): The volume percentage V" of austenite in the sample after heat treatment at 600℃ was calculated γ =16.17%, according to formula (1) V γ +V α =100% The volume percentage of martensite in the sample after heat treatment at 600℃ is calculated as V" α =83.83%. The lattice constants of martensite and austenite remain unchanged, that is, a α =2.873, a γ =3.593,
[0078] (3) V' α 、V' γ , V” α , V” γ , Substitute the numerical value into formula (2): The volume change rate of the martensite-austenite dual-phase steel after heat treatment at 600°C is calculated to be ΔV%=0.003%.
[0079] Table 3. Diffraction peak intensities of martensite and austenite in samples after different heat treatments measured by XRD
[0080]
[0081]
[0082] The volume percentages of martensite and austenite in the samples obtained by different heat treatment processes in Examples 1 to 3 and the volume change rates of the samples are shown in Table 4:
[0083] Table 4. Volume change rate of samples obtained by different heat treatment processes
[0084]
[0085] Figure 1It is the organization diagram (OM diagram) under the optical microscope of the original martensite-austenite dual-phase steel sample of the present invention and the dual-phase steel sample after the process heat treatment of Examples 1 to 3; wherein (a), (b), (c), and (d) respectively represent the original martensite-austenite dual-phase steel sample, the sample after the process heat treatment according to Example 1, the sample after the process heat treatment according to Example 2, and the sample after the process heat treatment according to Example 3. It can be seen that compared with the original martensite-austenite dual-phase steel sample, the microstructure of the sample changes after the heat treatment. In addition, Figure 1 The microstructures of (b), (c), and (d) are obviously different, which is due to the different contents of martensite and austenite in the samples obtained by different heat treatment processes.
[0086] Figure 2 The SEM images of the original martensite-austenite dual-phase steel sample of the present invention and the sample after heat treatment according to the process of Examples 1 to 3, wherein (a), (b), (c), and (d) represent the original martensite-austenite dual-phase steel sample, the sample after heat treatment according to the process of Example 1, the sample after heat treatment according to the process of Example 2, and the sample after heat treatment according to the process of Example 3, respectively. It can be seen that the SEM images of the heat-treated sample and the original martensite-austenite dual-phase steel sample are quite different. This is because after heat treatment, the martensite phase in the original sample transforms to the austenite phase, making its microstructure different. In addition, Figure 2 The SEM images of (b), (c), and (d) are also quite different, and the microstructures are obviously different. This is because the contents of martensite and austenite in the samples obtained by different heat treatment processes are different.
[0087] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment, characterized in that The following steps are involved: (1) XRD tests were performed on martensite-austenite dual-phase steel samples (hereinafter referred to as "original dual-phase steel samples"). The parameters of the XRD tests included the diffraction peak intensities of martensite and austenite in the original dual-phase steel samples: Iγ`(200), Iγ`(220), Iγ`(311), Iα`(200), and Iα`(211), where α represents martensite and γ represents austenite; Iγ`(200) represents the diffraction peak of the austenite (200) crystal plane in the original dual-phase steel samples. intensity, Iγ`(220) represents the diffraction peak intensity of the austenite (220) crystal plane in the original dual-phase steel sample, Iγ`(311) represents the diffraction peak intensity of the austenite (311) crystal plane in the original dual-phase steel sample, Iα`(200) represents the diffraction peak intensity of the martensite (200) crystal plane in the original dual-phase steel sample, and Iα`(211) represents the diffraction peak intensity of the martensite (211) crystal plane in the original dual-phase steel sample; the volume percentage V' of austenite in the original dual-phase steel sample is calculated γ and the volume percentage of martensite V' α ; (2) heat treating the original dual-phase steel sample of step (1), and performing XRD test on the heat treated sample, the method and test conditions are the same as step (1); the test parameters include the diffraction peak intensities of martensite and austenite in the heat treated sample Iγ(200), Iγ(220), Iγ(311), Iα(200), and Iα(211), wherein α represents martensite and γ represents austenite; Iγ(200) represents the diffraction peak intensities of austenite (200) in the heat treated sample. The diffraction peak intensity of the austenite (220) crystal plane in the heat-treated sample is Iγ(220), the diffraction peak intensity of the austenite (311) crystal plane in the heat-treated sample is Iγ(311), the diffraction peak intensity of the martensite (200) crystal plane in the heat-treated sample is Iα(200), and the diffraction peak intensity of the martensite (211) crystal plane in the heat-treated sample is Iα(211). The volume percentage of austenite in the heat-treated sample V" is calculated. γ and the volume percentage of martensite V" α ; (3) The volume percentage of martensite in the original dual-phase steel sample V' α and the volume percentage of austenite V' γ , Volume percentage of martensite in the sample after heat treatment V" α and the volume percentage of austenite V" γ and the martensite lattice constant a α and austenite lattice constant a γ Substitute into formula (2) The volume change rate of martensite-austenite dual-phase steel after heat treatment is calculated.
2. The method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment according to claim 1, characterized in that During the XRD test, the metal target used was Co target.
3. The method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment according to claim 1, characterized in that The volume percentage V' of austenite in the original duplex steel sample was calculated according to the five-line six-pair method in the ferrous metallurgy industry standard YB / T 5338-2019 of the People's Republic of China. γ And the volume percentage of austenite in the sample after heat treatment V" γ , the volume percentage of austenite in the original dual-phase steel sample V' γ , the volume percentage of austenite in the sample after heat treatment V" γ Substitute into formula (1) V γ +V α =100%, and the volume percentage of martensite in the original dual-phase steel sample V' is calculated respectively. α and the volume percentage of martensite in the sample after heat treatment V" α ; The martensite lattice constant a is obtained according to the standard PDF card in the International Diffraction Data Center database α and austenite lattice constant a γ .
4. The method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment according to claim 1 or 3, characterized in that According to the five-line six-pair method in YB / T 5338-2019, according to formula (3) Calculate the volume percentage V of austenite in the sample γ In formula (3), V γ is the volume percentage of austenite in the sample, V c Indicates the volume percentage of the total amount of carbide phase in the sample. The carbon content of the martensite-austenite dual-phase steel used in the experiment is less than 0.01%. c Ignore, so V c =0; Indicates the martensite phase in the sample (hkl) i The diffraction peak intensity of the crystal plane; Indicates the austenite phase in the sample (hkl) i Diffraction peak intensity of crystal plane; G represents austenite phase (hkl) i Crystal plane and martensite phase (hkl) i The ratio of intensity-related factors corresponding to the crystal planes; The G value, the ratio of the diffraction peak intensity of martensite to austenite in the original dual-phase steel sample Substitute into formula (3) The volume percentage V' of austenite in the original dual-phase steel sample is obtained γ ; The G value and the ratio of the diffraction peak intensity of martensite to austenite in the heat treated sample Substitute into formula (3) Get the volume percentage V" of austenite in the sample after heat treatment γ .
5. The method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment according to claim 4, characterized in that Ratio of diffraction peak intensity between martensite and austenite in original dual-phase steel sample include Each pair Substitute the value of and the corresponding G value into formula (3) Calculate V' once γ , a total of 6 V' γ value, and then calculate the 6 V' γ The arithmetic mean of the values is the volume percentage V' of austenite in the original duplex steel sample. γ .
6. The method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment according to claim 4, characterized in that The ratio of the diffraction peak intensity of martensite to austenite in the sample after heat treatment include Each pair Substitute the value of and the corresponding G value into formula (3) Calculate V once γ , a total of 6 V" γ value, and then calculate 6 V" γ The arithmetic mean of the values is the volume percentage V" of austenite in the sample after heat treatment. γ .
7. The method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment according to claim 1, characterized in that The martensitic steel samples were heat treated using a resistance furnace with a model of BSK-83 and a rated power of 9KW.
8. The method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment according to claim 1 or 7, characterized in that The martensitic steel sample was heat treated in a resistance furnace with a model of BSK-83 and a rated power of 9KW. The temperature was raised to 500-600°C at a heating rate of 10°C / min, and kept at 500-600°C for 180 minutes. The sample was then taken out and cooled to room temperature in the air to obtain a heat-treated sample.
9. The method for evaluating the volume change rate of martensite-austenite dual-phase steel after heat treatment according to claim 8, characterized in that The temperature of the heat treatment is 500°C, 550°C or 600°C.
Citation Information
Cited By
Method, system, equipment and medium for quantitatively evaluating austenite stability of steel
CN122063245A